2002
DOI: 10.1523/jneurosci.22-01-00248.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Tripotential Glial-Restricted Precursor (GRP) Cell and Glial Development in the Spinal Cord: Generation of Bipotential Oligodendrocyte-Type-2 Astrocyte Progenitor Cells and Dorsal–Ventral Differences in GRP Cell Function

Abstract: We have found that the tripotential glial-restricted precursor (GRP) cell of the embryonic rat spinal cord can give rise in vitro to bipotential cells that express defining characteristics of oligodendrocyte-type-2 astrocyte progenitor cells (O2A/OPCs). Generation of O2A/OPCs is regulated by environmental signals and is promoted by platelet-derived growth factor (PDGF), thyroid hormone (TH) and astrocyte-conditioned medium. In contrast to multiple observations indicating that oligodendrocyte precursor cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(119 citation statements)
references
References 56 publications
6
111
2
Order By: Relevance
“…We found that in AP-infected cells, approximately 16 Ϯ 2% were myelin proteolipid protein (PLP) -immunoreactive and 13 Ϯ 4% were GalCimmunoreactive 5 days after the cells were cultured in oligodendrocytepromoting conditions. These numbers are consistent with the extent of oligodendrocyte differentiation observed in other experiments (Rao et al, 1998;Gregori et al, 2002). In contrast, in Hes1-infected cells, there were very few PLP-or GalC-immunoreactive cells (Ͻ1%, Figs.…”
Section: Hes1 Acts On Grps To Inhibit Oligodendrocyte Differentiationsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that in AP-infected cells, approximately 16 Ϯ 2% were myelin proteolipid protein (PLP) -immunoreactive and 13 Ϯ 4% were GalCimmunoreactive 5 days after the cells were cultured in oligodendrocytepromoting conditions. These numbers are consistent with the extent of oligodendrocyte differentiation observed in other experiments (Rao et al, 1998;Gregori et al, 2002). In contrast, in Hes1-infected cells, there were very few PLP-or GalC-immunoreactive cells (Ͻ1%, Figs.…”
Section: Hes1 Acts On Grps To Inhibit Oligodendrocyte Differentiationsupporting
confidence: 91%
“…G3PDH (25 cycles) was used as a control. Herrera et al, 2001;Gregori et al, 2002). Our results suggest that Hes1 acts at the GRP stage to promote astrocyte differentiation.…”
Section: Hes1 Acts On Grps To Inhibit Oligodendrocyte Differentiationmentioning
confidence: 61%
See 1 more Smart Citation
“…Differentiation here occurred in the presence or absence of FBS. Development of tectal oligodendrocytes thus appears to be fundamentally different from mammalian oligodendrocytes arising under the scheme involving O-2A progenitor cells, where FBS inhibits their differentiation (Raff et al, 1983;Gregori et al, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…First, glial progenitors that can generate oligodendrocytes are present at E13 in dorsal spinal cord (Lee et al, 2000;Gregori et al, 2002), indicating that non-pMN foci also have at least the potential to generate oligodendrocytes. Second, PDGFR␣ expression may not be obligate for all oligodendrocyte progenitors, because a population of OPCs emerge from the olfactory anlage independent of PDGFR␣ (Spassky et al, 2001).…”
Section: Opc Origins and Pdgfr␣mentioning
confidence: 99%